2021
DOI: 10.1021/acs.biomac.1c01327
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde-Functional Diblock Copolymer Nano-objects via RAFT Aqueous Dispersion Polymerization

Abstract: This is a repository copy of Aldehyde-functional diblock copolymer nano-objects via RAFT aqueous dispersion polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 64 publications
2
36
0
Order By: Relevance
“…This approach means that the same cis -diol-functional worm gel precursor was used to produce each aldehyde-functional worm gel examined in this study, which eliminates batch-to-batch variability. Moreover, 1 H NMR spectroscopy studies (data not shown) confirmed that a sample of 100% aldehyde-functional PAGEO5MA 26 -PHPMA 250 worms reported in our prior study 69 remained stable with respect to aerial oxidation for at least one year when stored at ambient temperature. TEM studies confirmed that there was no discernible change in morphology after oxidation (Fig.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…This approach means that the same cis -diol-functional worm gel precursor was used to produce each aldehyde-functional worm gel examined in this study, which eliminates batch-to-batch variability. Moreover, 1 H NMR spectroscopy studies (data not shown) confirmed that a sample of 100% aldehyde-functional PAGEO5MA 26 -PHPMA 250 worms reported in our prior study 69 remained stable with respect to aerial oxidation for at least one year when stored at ambient temperature. TEM studies confirmed that there was no discernible change in morphology after oxidation (Fig.…”
Section: Resultssupporting
confidence: 74%
“…The former worms were subsequently oxidized with sodium periodate targeting periodate/ cis -diol molar ratios of 0.10, 0.20, 0.30 or 0.50 using a previously reported protocol developed for crosslinked PGEO5MA 26 -PHPMA 350 -PEGDMA 20 vesicles. 69 In each case, the extent of oxidation was determined by 1 H NMR spectroscopy (Fig. S10 † ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, we have obtained a 2-(hydroxyimino)­aldehyde butyl methacrylate (HIABMA) monomer, which has a p K a of the oxime group that is at least 3 orders of magnitude higher than that of acrylic and benzoic acids (see herein), provides multiple sites for hydrogen bonding, has potential for metal chelation, and exhibits a wavelength-dependent photochemical behavior (i.e., E / Z oxime isomerism and an unusually chemoselective Norrish–Yang cyclization). , In other words, HIABMA-based amphiphilic block copolymers are good candidates to obtain temperature- and light-sensitive copolymers that aggregate by either pH or solvent switch, potentially leading to different nanostructures with different properties that are also stable at physiological pH. The novelty of the HIABMA group with respect to monomers bearing simple aldehydes or oximes , derives from the two functional groups being adjacent, which has consequences on aldehyde photochemistry, oxime acidity, and, possibly, on metal chelation (the latter is an ongoing investigation in our group) . Potential applications of HIABMA copolymers are, therefore, quite different from the widely investigated polymeric prodrugs based on CN conjugation chemistry.…”
Section: Introductionmentioning
confidence: 99%